Exploring the Relationship Between Psychological Maturity and Leadership Personality Traits – A Discourse Analysis - Sen, Subhasis; Banerjee, Sweta (Prabandhan: Indian Journal of Management, 2024)
Purpose : The study here used discourse analysis (DA), a qualitative approach addressed by psychological researchers, to understand and interpret the meaning associated with psychological maturity and leadership personality traits and to explore the relationship between them. Methodology : DA has the capability of innovatively addressing global psychology issues like maturity and personality. The data were collected from research journals on psychology and human resource management published by eminent psychological researchers to ensure the content validity of the study. Key Findings : Three levels of psychological maturity (PM) during adulthood and pertaining to leaders were found to be : socialization, self-authorization, and self-transformation. The transformation from employee to leadership role induced responsibility and emotional stability in an individual. Personality traits like extraversion, conscientiousness, openness to experience, neuroticism, and agreeableness vary from males to females in a leadership role. Practical Implications : In today’s volatile world of uncertainties, complexities, and ambiguities (VUCA), multifarious occupational perceptions evolved into leadership maturity. A leader must exhibit calmness and tackle negative feelings causing stress effectively to build emotional stability. Over time, such changes in leadership traits impacted the levels of psychological maturity. Originality : The mediators identified in the study were conscientiousness, emotional stability, and openness to experience, which stimulated the strength of association between psychological maturity and leadership personality traits.